Longer Neurophysiological vs. Clinical Recovery Following Sport Concussion - Ntikas, Michail; Hunter, Angus M.; Gallagher, Iain J.; Di Virgilio, Thomas G. (Frontiers in Sports and Active Living, 2021)
Objectives: The objective of this study was to assess if injury-related alterations in the Sport Concussion Assessment Tool-5 (SCAT5) are matched by changes in transcranial magnetic stimulation-derived intracortical inhibition. We hypothesised that neurophysiological measures would take longer to return to normal than recovery assessed by the SCAT5 following sport related concussion (SRC). Methods: Thirteen male contact sport athletes (20.5 ± 4.5 years), who reported a concussion were recruited from local Rugby and American football clubs. Participants were tested at 4 timepoints throughout the concussion recovery period: within 24 h of concussion (day 0), and at 7, 9, and 11 days after concussion. All participants completed the SCAT5 and underwent TMS to assess cortical silent period duration (CSp), a measure of intracortical inhibition. Results: After concussion CSp significantly declined from day 0 (122 ± 28 ms) to day 11 (106 ± 15 ms) [F(3, 33) = 7.80, p < 0.001]. SCAT5 measures of symptom number and severity were significantly decreased [symptom number: χ(3)2 = 30.44, p < 0.01; symptom severity: χ(3)2 = 25.75, p < 0.001] between the day 0 timepoint and each of the other timepoints. SCAT5 balance errors (mBESS) decreased significantly [F(3, 33) = 19.55, p < 0.001] between the day 0 timepoint and each of the other timepoints. CSp and SCAT5 recovery patterns were different. SCAT5 domains recovered faster showing no further significant changes after day 7, whilst CSp was still decreasing between days 7 and 9. Due to the small sample size we also used a Bayesian linear model to investigate the recovery of CSp and mBESS. The posterior distribution of our Bayesian model provided evidence that CSp decreased at day 7 and it continued to decrease at day 9, unlike mBESS which decreased at day 7 and then reached a plateau. Conclusion: There are clinically important discrepancies between clinical and neurophysiological measures of concussion recovery. This finding has important implications for return to play (RTP) protocols and the prevention of complications after sport concussion.